Reduced NK Cell Cytotoxicity by Papillomatosis-Derived TGF-β Contributing to Low-Risk HPV Persistence in JORRP Patients - Wu, Xunyao; Xiao, Yang; Guo, Dan; Zhang, Zixin; Liu, Meiyu (Frontiers in Immunology, 2022)
The role of natural killer (NK) cells in juvenile-onset recurrent respiratory papillomatosis (JORRP) patients remains inclusive. In this study, we find increased NK cells percentage, particular CD11b-CD27- (DN) subsets in peripheral blood of JORRP patients and associated with disease activity. RNA-sequencing shows a downregulated “Natural killer cell mediated cytotoxicity” feature in JORRP tumors. We also find impaired cytotoxic capacity and lower expression of NK cells activating receptors including NKp30, NKp46. Higher transforming growth factor-beta 1 (TGF-β1) is found both in plasma or tumor tissues of JORRP and anti-TGF-β1 antibody could restore NK cell cytolytic activity and up-regulate NKp30 and NKG2D expression. Also, we find a significantly higher CXCR6 on NK cells in tumors compared with peripheral blood. Finally, RT-PCR analysis show that both HPV6-E6-E7 and HPV11-E6-E7 overexpression leads to higher TGF-β1 expression compared with control SNU-1076 cell line and higher CXCR6 expression is detected on NKs coculture with HPV11-E6-E7 overexpressing cells. In conclusion, we demonstrate that TGF-β1 by papillomatosis lead to decreased NK cells cytotoxicity through downregulating NK cells activating receptors in JORRP patients.